2008
DOI: 10.1016/j.disc.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Values of coefficients of cyclotomic polynomials

Abstract: Let a(k, n) be the k-th coefficient of the n-th cyclotomic polynomials. In 1987, J. Suzuki proved that {a(k, n) | n, k ∈ N} = Z. In this paper, we improve this result and prove that for any prime p and any integer l ≥ 1, we have {a(k, p l n) | n, k ∈ N} = Z.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…In 1987, J. Suzuki [19] proves that in fact, any integer can be a coefficient of a cyclotomic polynomial of a certain degree. The result was further improved more recently by C.-G. Ji and W.-P. Li [13].…”
Section: Introductionmentioning
confidence: 79%
“…In 1987, J. Suzuki [19] proves that in fact, any integer can be a coefficient of a cyclotomic polynomial of a certain degree. The result was further improved more recently by C.-G. Ji and W.-P. Li [13].…”
Section: Introductionmentioning
confidence: 79%
“…✷ Remark 1. If one specializes the above proof to the case m = p e , a proof a little easier than that given in part I [2] is obtained, since it does not involve a case distinction between m is odd and m is even as made in part I. This is a consequence of working modulo x 2p 1 , rather than modulo x 2p 1 +1 .…”
Section: The Proof Of Theoremmentioning
confidence: 89%
“…In 1987 Suzuki [4] proved that S(1) = Z. Recently the first two authors [2] proved that S(p e ) = Z with p e a prime power.…”
Section: Introductionmentioning
confidence: 99%
“…It is not difficult, see Suzuki [22], to adapt his argument so as to show that every integer shows up as a coefficient, that is {a n (k): n 1, k 0} = Z. This was recently generalized by Ji and Li [11], who showed that if p e is a prime power, then {a p e n (k): n 1, k 0} = Z. This result on its turn was generalized by Ji, Li and Moree [12], who showed that, with m any positive integer, a mn (k): n 1, k 0 = Z and c mn (k): n 1, k 0 = Z.…”
Section: Sizable Coefficientsmentioning
confidence: 93%